Atypical Enteropathogenic Escherichia coli Strains form Biofilm on Abiotic Surfaces Regardless of Their Adherence Pattern on Cultured Epithelial Cells - Culler, Hebert F. (Hindawi Publishing Corporation, 2014)
The aim of this study was to determine the capacity of biofilm formation of atypical enteropathogenic Escherichia coli (aEPEC) strains on abiotic and biotic surfaces. Ninety-one aEPEC strains, isolated from feces of children with diarrhea, were analyzed by the crystal violet (CV) assay on an abiotic surface after 24 h of incubation. aEPEC strains representing each HEp-2 cell type of adherence were analyzed after 24 h and 6, 12, and 18 days of incubation at 37°C on abiotic and cell surfaces by CFU/cm(2) counting and confocal laser scanning microscopy (CLSM). Biofilm formation on abiotic surfaces occurred in 55 (60.4%) of the aEPEC strains. There was no significant difference in biofilm biomass formation on an abiotic versus prefixed cell surface. The biofilms could be visualized by CLSM at various developmental stages. aEPEC strains are able to form biofilm on an abiotic surface with no association with their adherence pattern on HEp-2 cells with the exception of the strains expressing UND (undetermined adherence). This study revealed the capacity of adhesion and biofilm formation by aEPEC strains on abiotic and biotic surfaces, possibly playing a role in pathogenesis, mainly in cases of persistent diarrhea.